How can Customer Analytics Capabilities Influence Organizational Performance? A moderated mediation analysis - Alamir Costa Louro; Marcelo Moll Brandão; Jurij Jakli\u010D; Arthur Sarcinelli (BBR: Brazilian Business Review)
A theoretical model is proposed to test the relationship between Customer Analytics Capabilities and Market Orientation with Organizational Performance, encompassing Marketing Capabilities as a mediator mechanism moderated by Environmental Dynamism. Its contribution lies in the test of this mediation in different types of industries in Brazil, by using SmartPLS software for structural equation modeling (SEM) and IBM SPSS with PROCESS macro for more in-depth insights. The results confirm the moderated mediation but show different behaviors about the direct effect for Customer Analytics Capabilities and Market Orientation, which suggest future studies. The study supports a better understanding of some of the diverse capabilities types and proposes an adaptive new one, Customer Analytics Capabilities, which is the final insertion of the Analytics concept in Marketing and Strategy disciplines.